2007
DOI: 10.1016/j.asr.2006.09.031
|View full text |Cite
|
Sign up to set email alerts
|

Solar flare detection system based on global positioning system data: First results

Abstract: A solar flare detector has been developed using the Global Positioning System (GPS) capabilities to monitor the ionospheric Total Electron Content (TEC). It is based on obtaining the variation of the vertical TEC data with respect to the previous sidereal day and then, on performing a second order time difference to obtain the information of the instantaneous TEC changes. The detector can be applied looking for solar flares backwards or in real time as well. To make a first assessment of the solar flare detect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 6 publications
1
16
0
Order By: Relevance
“…In this regard, tests feeding the UPC prediction model with physical information including indexes of solar/geomagnetic activity, such as Kp and Solar Flux, are currently being conducted. Also in this context, a detector of solar flares facing the earth that may be used to input additional physical information into the prediction model has been developed by the authors [see García‐Rigo et al , 2008, 2006]. Apart from that, further improvement could be obtained by using a geomagnetic grid rather than a geographic one or by using a subset of the regression coefficients (for instance, they could be determined by feature selection [ Hastie et al , 2001]).…”
Section: Conclusion and Further Stepsmentioning
confidence: 99%
“…In this regard, tests feeding the UPC prediction model with physical information including indexes of solar/geomagnetic activity, such as Kp and Solar Flux, are currently being conducted. Also in this context, a detector of solar flares facing the earth that may be used to input additional physical information into the prediction model has been developed by the authors [see García‐Rigo et al , 2008, 2006]. Apart from that, further improvement could be obtained by using a geomagnetic grid rather than a geographic one or by using a subset of the regression coefficients (for instance, they could be determined by feature selection [ Hastie et al , 2001]).…”
Section: Conclusion and Further Stepsmentioning
confidence: 99%
“…The whole week from 16 January 2005 was dominated by one single big sunspot group, which was clearly visible on the solar disk (http://sidc.oma.be) [see, e.g., Garcia‐Rigo et al , 2007]. The group produced an M‐ and X‐flaring period with a wide impact on both solar‐terrestrial physical system and technology.…”
Section: The 20 January 2005 Sudden Space Weather Eventmentioning
confidence: 99%
“…The observation of permanent GPS tracking stations, under the management of the International GPS Service (IGS), has become a powerful tool for ionospheric research, providing good, continuous worldwide coverage at low cost to the users. Many authors have used GPS for total electron content (TEC) observations and in the study of ionospheric space weather (Aarons et al, 1997;Ho et al, 1998;Jakowski et al, 1999;Afraimovich et al, 2000;Meza et al, 2005), especially for SITEC properties (Afraimovich, 2001(Afraimovich, , 2002(Afraimovich, , 2000Zhang et al, 2002;Xiao, 2003, 2005;Liu et al, 2004Liu et al, , 2006Wan et al, 2005;García Rigo et al, 2007). In particular, Zhang et al (2002) analysed the ionospheric response to a solar flare similar to the flare used in this work; they found that the enhancement of TEC tended to depend on latitude, longitude, and the solar zenith angle of the subionospheric point, but not symmetrically, and it was smaller in the local morning than in the afternoon.…”
Section: Introductionmentioning
confidence: 99%